Ectopic adipose tissue: frequency and clinical characteristics of obesity phenotypes in patients - V. I. Podzolkov; A. E. Bragina; Yu. N. Rodionova; K. K. Osadchiy; M. K. Vasilchenko; A. P. Muravlev; V. S. Ananeva; A. V. Balutskaya; M. O. Pilipenko (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To study the frequency and clinical characteristics of ectopic obesity in patients with different body weights and hypertension (HTN).Material and methods. The study included 326 patients (145 men and 181 women, mean age 63±8 years). Patients underwent chest and retroperitoneal space computed tomography with calculation of the volumes of perivascular adipose tissue (AT) (PVAT), pericardial AT (PAT) and perirenal fat thickness (PFT) using specialized software QCT Pro Tissue Composition Module (Mindways Software, USA). PAT volume ≥3,2 cm3, PVAT volume ≥0,4 cm3, PFT ≥1,91 cm were considered criteria for pericardial (PCO), perivascular (PVO) and perirenal (PRO) obesity.Results. When studying the prevalence of ectopic (EO) and abdominal (AO) obesity phenotypes, patients were divided into groups: 1) with isolated EO without AO (n=17), 2) with PCO and AO (n=31), 3) with PVO and AO (n=22), 4) with PRO and AO (n=33), 5) with mixed EO (PKO+PVO, or PKO+PRO, or PVO+PRO, or PKO+PVO+PRO) and AO, 6) with isolated AO without EO (n=74), 7) without obesity (n=32). Isolated EO was significantly more common in individuals with normal and overweight compared to patients with obesity: 8,9 and 12 vs 1,1% (p=0,001), respectively. The prevalence of the mixed EO+AO phenotype in obese patients was significantly higher than in patients with normal and overweight as follows: 41,7 vs 19,6 and 21,7% (p=0,001), respectively. In patients with HTN, PVO+AO was significantly more common compared to patients without HTN as follows: 12,8 vs 3% (p=0,001), respectively.Conclusion. The study results indicate the heterogeneity of the distribution of obesity phenotypes in people with different body mass index, which emphasizes the importance of taking into account all its variants, including EO, for timely and adequate cardiovascular risk assessment.